Metformin as a potential agent for modulating the faulty endometriotic mesenchymal stem cells: A case-control study - Parisa Mashayekhi; Mehrdad Noruzinia; Sepideh Khodaverdi (International Journal of Reproductive BioMedicine, 2022)
Abstract Background: According to stem cell theory, it seems that the proliferation/differentiation imbalance in endometrial mesenchymal stem cells (enMSCs) is the leading cause of endometriosis, so targeting them to modulate stemness-relevant factors seems to be a wise choice for endometriosis treatment. Objective: We aimed to investigate the effects of metformin on stemness properties of enMSCs by evaluating the expression profile of stemness-related genes and microRNAs (miRNAs). Materials and Methods: In this case-control study, MSCs were isolated from the eutopic endometrium of 3 endometriotic and 3 healthy women. After their characterization and culture, they were treated with 0.1, 1, and 10 mM metformin for 72 hr. Finally, the expression of octamer-binding transcription factor (OCT) 4A, OCT4B, OCT4B1, sex determining region Y-Box transcription factor 2, nanog homeobox, microRNA-200b, microRNA-145, and lethal-7b were analyzed by quantitative reverse transcription-polymerase chain reaction. Results: Metformin modulated the expression of stemness-related genes and miRNAs, OCT4A, OCT4B, OCT4B1, sex determining region Y-Box transcription factor 2, nanog homeobox, microRNA-200b, microRNA-145, and lethal-7b in enMSCs, especially at 1 and 10 mM concentration. Notably, metformin had a paradoxical effect on normal enMSCs. Conclusion: We showed that metformin could modulate the expression of deregulated genes and miRNAs in faulty enMSCs, and restore their skewed self-renewal/differentiation balance, so it might be a promising drug for endometriosis treatment. The paradoxical effect of metformin on enMSCs and normal enMSCs might be because of their different metabolic patterns, so it requires further investigation to illustrate.